An Analysis of Formative Assessment in Teaching English Used by Teacher - Putri Meldia Putri Meldia; Melyann Melani Melyann Melani (PANYONARA: Journal of English Education, 2022)
The research is aimed at analyzing about the process of implementing classroom assessment and conducting formative assessment in English as Foreign Language (EFL) at Islamic Junior High School. The approach of this study used a qualitative research. One of the qualitative research designs applied in this study was case study design. The data were collected through interviews, observations, and documentation to an English teacher, as well as some observed students. Methodological triangulations were used to validate the data collected, which was then analyzed qualitatively and reported descriptively. The findings revealed that there are three points related to this research; the teacher has already understand about the concept of formative assessment, the teacher has already conducted the formative assessment in EFL classroom, and the challenges faced by teacher while conducting the formative assessment in EFL classroom . The challenges were the teacher' incapacity to design activities for the classroom and evaluation standards for including formative assessment, the enormous number of students in each class makes it impossible to provide quick feedback to them or incorporate comments into group activities, and given the constrained amount of class time, formative assessment is time-consuming and cannot be used. especially in light of a centralized educational system that prioritizes summative rather than formative assessment